North-South trade-related technology diffusion: Virtuous growth cycles in Latin America - Maurice Schiff; Yanling Wang (Institute for the Study of Labor (IZA), 2010)
This paper examines the impact on TFP in Latin America and the Caribbean (LAC) and in other developing countries (DEV) of trade-related foreign R&D (NRD), education and governance. The measures of NRD are constructed based on industry-specific R&D in the North, North-South trade patterns, and input-output relations in the South. The main findings are: i) education and governance have a much larger direct effect on TFP in LAC than in DEV, while the opposite holds for the North's R&D; and ii) education and governance have an additional impact on TFP in R&D-intensive industries through their interaction with NRD in LAC but not in DEV. These interaction effects imply that increasing the level of any of the three policy variables - education, governance or openness - result in virtuous growth cycles. These are smallest under an increase in trade, education or governance, are stronger under an increase in two of these three policy variables, and are strongest under an increase in all three variables.
Keywords: F15; O19; O33; 330; Trade; technology diffusion; growth; Latin America; Technologietransfer; Innovationsdiffusion; Nord-Süd-Beziehungen; Bildungsökonomik; Good Governance; Produktivität; Wirtschaftswachstum; Lateinamerika; Karibische Staaten